Infectious disease symptoms and microbial carriage among French medical students travelling abroad: A prospective study. Issue 34 (March 2020) - Dao, Thi Loi; Hoang, Van Thuan; Ly, Tran Duc Anh; Magmoun, Amal; Canard, Naomie; Drali, Tassadit; Fenollar, Florence; Ninove, Laetitia; Raoult, Didier; Parola, Philippe; Courjon, Johan; Gautret, Philippe
Abstract: Background: In France, no previous studies have focused specifically on health problems among medical students during internships abroad including the clinical symptoms suggestive of infectious diseases and the acquisition of pathogen carriage. Methods: Clinical follow up and qPCR based respiratory, gastrointestinal and vaginal pathogen carriage before and after travel were prospectively assessed in a cohort of medical students departing from Marseille, France. Results: 134 students were included. 73.9%, 38.8% and 5.0% of students reported gastrointestinal, respiratory and vaginal symptoms, respectively. The acquisition rate of Enteroaggregative Escherichia coli (EAEC) and Enteropathogenic E. coli (EPEC) was 53% and 41%, respectively. The acquisition of respiratory viruses was low but associated with persisting symptoms, while bacterial acquisition ranged from 3.3% for Streptococcus pyogenes to 15.0% for Haemophilus influenzae . Gardnerella vaginalis and Atopobium vaginae acquisition rates were 7.7% and 14.3% respectively. Five students (5.1%) had molecular quantification criteria for bacterial vaginosis on return. Conclusion: This preliminary study demonstrates that besides the known risk of gastrointestinal and respiratory infections and associated changes in intestinal and respiratory microbiota, medical students abroad may also experience changes in vaginal microbiota leading, in some cases, to clinical symptoms or the acquisition of bacterial vaginosis, which may be asymptomatic.